Relationship between Peer Friends and Learning Motivation - Muhammad Aldy Mubharak; Muswardi Rosra; Redi Eka Andriyanto (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The purpose of this study was to determine the relationship between peer relationships with learning motivation in class VIII Bandar Lampung Middle School 9 academic year 2018/2019. This research method is quantitative. The study population was 207 students and a sample of 74 students was determined by simple random sampling technique. Data collection techniques use a scale of peer interaction and motivation to learn. The data analysis technique in this study uses Product moment correlation. The results show there is a positive and significant relationship between peer relationships with motivation to learn. This is indicated by the value of r count r table (0.682 0.227) the significance level of 0.05. then Ho is rejected and Ha is accepted. The conclusion is that there is a positive and significant relationship between peer relationships with learning motivation in class VIII Bandar Lampung SMPN 9 academic year 2018/2019.Tujuan penelitian ini adalah untuk mengetahui hubungan antara pergaulan teman sebaya dengan motivasi belajar pada siswa kelas VIII SMP Negeri 9 Bandar Lampung tahun ajaran 2018/2019.Metode penelitian ini bersifat kuantitatif.Populasi penelitian sebanyak 207 siswa dan sampel berjumlah 74 siswa yang ditentukan dengan teknik simple random sampling.Teknik pengumpulan data menggunakan skala pergaulan teman sebaya dan motivasi belajar.Teknik analisis data pada penelitian ini menggunakan korelasi Product moment.Hasil menunjukkan terdapat hubungan positif dan signifikan antara pergaulan teman sebaya dengan motivasi belajar. Hal ini ditunjukkan dari nilai rhitung rtabel (0,6820,227 )taraf signitifkan 0,05. maka Ho ditolak dan Ha diterima. Kesimpulannya adalah terdapat hubungan yang positif dan signifikan antara pergaulan teman sebaya dengan motivasi belajar pada siswa kelas VIII SMPN 9 Bandar Lampung tahun ajaran 2018/2019. Kata kunci: bimbingan konseling, pergaulan teman sebaya, motivasi belajar